Study Of The Implementation Of Additive Manufacturing At PROTON Using Analytic Hierarchy Process - Rahim, Siti Lydia (2017)
Additive Manufacturing (AM) is the direct production of finished goods using additive fabrication techniques. AM done in parallel batch production can provide a large advantage in both speed and cost. Currently, the efforts to utilize the AM concept and technology have several problems, particularly in the Malaysian automotive industry. Such existing problems have discouraged the enhancement of process development of the automotive industry. In providing the solution, by adopting the AM concept, there is potential to expedite the process development of automotive parts and move towards mass customization. These issues have been discovered through the discussion with Malaysian AM experts and also with the Malaysian automotive manufacturer which is PROTON and its vendor. This research presents an overview of the implementation of the AM and the critical decision factors in implementing AM in PROTON. The Analytic Hierarchy Process (AHP) is a theory of decision-making through pairwise comparisons and relies on the judgments of experts to derive priority scales. AHP is used in order to assess the priority scales affecting AM implementation. The four main factors that will affect the implementation were the financial aspect, which is included investment cost and maintenance cost. Technological aspect was the main factor of AM system selection and material. Employee response to change and impact on supply chain were sub-factors of the main of organization aspect, meanwhile design practice aspect was the main factor for impact on product design and operation activities. This research fulfills an identified information need and offers practical help to an organization to promote the acceptance and implementation of AM technology. PROTON and other industries can focus for further development of implementation.